Dietary Perception in Diabetes: A Cross-sectional Study of Patient Perceptions in a Tertiary Care Center at Delhi, India - Anshuman Srivastava; Abha Sharma; Aarushi Tanwar; Paridhi Malhotra; Smita Nath (Indian Journal of Medical Specialities, 2026)
Abstract Background: Dietary behavior plays a crucial role in diabetes management; however, patients’ perceptions and beliefs about common food items often influence adherence. Misconceptions regarding fruits, sweets, and traditional foods remain prevalent in India. The study was planned with an aim of assessing the dietary myths, beliefs, and perceptions regarding common food items among patients with diabetes mellitus attending a tertiary care center in Delhi. Methodology: A cross-sectional study was conducted among 210 patients with diabetes using a structured questionnaire. Proportions were calculated, and associations with demographic variables were analyzed using the Chi-square test. Results: A total of 210 participants were included, with a predominance of older adults and a near-equal gender distribution; most were educated and on oral hypoglycemic therapy. High levels of misconceptions were observed, with 70.9% believing jaggery is safer than sugar and 63.3% considering fruits harmful in diabetes. Awareness was high for traditional foods such as turmeric (85.7%) and ginger (82.4%), but low for newer concepts, such as probiotics (34.3%) and chia seeds (28.1%). Misbeliefs persisted regarding dried fruits, sugar-free products, and the exclusion of rice. Cultural beliefs were prominent, with many participants attributing diabetes to excessive tea consumption or believing that bitter foods can reduce blood glucose. Education level showed a significant association with glycemic index awareness ( P = 0.021), whereas age and gender were not significantly associated. Conclusion: The study highlights a substantial burden of dietary myths and a significant knowledge–practice gap among patients with diabetes. While general awareness exists, it is often fragmented and influenced by cultural beliefs. Targeted dietary education is essential for improving diabetes management.